Thomas Kent letter to Jim Dinsmore regarding summer field reports, July 31, 1998 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1998)
Letter from Thomas Kent to Jim Dinsmore dated July 31, 1998. Kent reports a few sightings for the summer season. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1998.